Analysis of improvements in nitrogen use efficiency associated with 75 years of spring barley breeding - Bingham, I.J.; Karley, A.J.; White, P.J.; Thomas, W.T.B.; Russell, J.R. (European journal of agronomy, 2012)
► Breeding over 75 years has increased the nitrogen use efficiency of spring barley. ► The greater efficiency is the result of an increase in N uptake and utilization efficiencies. ► Improved utilization efficiency was more consistent across site-years than uptake efficiency. ► High uptake efficiency was correlated with a large post-anthesis N uptake. A retrospective analysis of the effects of nearly 75 years of breeding on the nitrogen use efficiency (NUE) of spring barley (Hordeum vulgare L.) was undertaken to identify physiological mechanisms governing NUE and targets for future improvement. Fifteen varieties, selected to be as genetically dissimilar as possible and to represent the breeding period from 1931 to 2005, were grown at three site-year combinations in the NE of Scotland. Varieties were grown with zero or 110kgNha−1 supplied as ammonium nitrate. Averaged across site-years, breeding was shown to increase yield and NUE (grainyieldNsupply−1) by 1 and 1.2% per year respectively in the presence of fertilizer. Mean grain weight was larger in modern compared to old varieties grown both with and without N fertilizer. The greater response of yield to fertilizer in modern varieties was associated with the production of more grainsm−2. Significant variation was found between genotypes in efficiencies of N uptake (NupE; N offtake per unit N supply) and N utilization (NutEg, grain yield per unit N offtake). Differences in NutEg contributed 60% to the variation in NUE, whilst NupE contributed 40%. The improvement in NutEg was mostly the result of increases in harvest index (HI) and was stable across environments. NupE was positively correlated with post-anthesis, but not pre-anthesis, dry matter accumulation and N uptake, which suggests that greater NupE of some varieties was the result of an increased N demand from a large grain sink. Across all varieties NupE was not related to NutEg suggesting that improvements in each may be selected independently. The results also indicated possible opportunities for improving the efficiency of pre-anthesis N uptake.